Active control of a backward facing step flow with plasma actuators - D'adamo, Juan Gastón Leonel (2014)
Active control over a backward facing step flow is studied experimentally by means of plasma based devices. The Reynolds number based on the step height h is 1520. An electrohydrodynamic actuator (EHD), dielectric barrier discharge (DBD) type, is flush mounted to the step wall. The DBD configuration adds momentum locally, normal to the separated shear layer, thus producing strong modifications downstream. The actuation is periodic and its frequency and amplitude are scrutinized to characterize the flow behavior under forcing. Measures of velocity fields for these flows are obtained from particle image velocimetry (PIV). As reported by previous works, the reattachment length shows an important reduction for an optimum forcing frequency. This value closely matches the shear layer flow natural frequency. On the other hand, the flow is less sensitive to the forcing amplitude though the analysis allows us to optimize the actuation in order to save power consumption.